α -Triangular Fuzzy Matrix and its Application - Thangaraj Beaula; J. Partheeban (International Journal of Mathematics And its Applications, 2018)
In this paper, a-triangular matrix is introduced with the help of α-cut of each its elements and the arithmetic operations on α-triangular matrices are defined. The determinant, adjoint, trace of it are also defined and with the help of it some properties are established. The correlation coefficient is defined between two triangular fuzzy numbers in terms of its a-cut and using this idea in α-triangular matrix it became feasible to solve a real life problem using analytic hierarchy process (AHP) for α[0,1].